2020
DOI: 10.1038/s41598-020-70661-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of partially silane-terminated polyurethanes reinforced with acid-treated halloysite nanotubes for transparent armour systems

Abstract: & oren e. petel in the present work, nanocomposites based on the partially silane-terminated polyurethanes reinforced with sulfuric acid-treated halloysite nanotubes were synthesized and evaluated as a potential candidate for transparent blast resistant configurations. The polyurethane must present high tensile ductility at high strain rates to be able to contain fragments and increase the survivability of the system. Gas-gun spall experiments were conducted to measure the dynamic tensile strength (spall stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…PU (approximately 32 wt.%), and that the bonding of the HNTs to the hard segments has been shown to promote the micro-phase separation of the nanocomposite 37 , we expect the occurrence of spherulites with a higher concentration of crystallized hard segments in the nanocomposite. Indeed, DSC results from our previous study 27 showed that the melting point of the hard phase crystallites was approximately 15 °C higher in the nanocomposite compared to that of the neat PU.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…PU (approximately 32 wt.%), and that the bonding of the HNTs to the hard segments has been shown to promote the micro-phase separation of the nanocomposite 37 , we expect the occurrence of spherulites with a higher concentration of crystallized hard segments in the nanocomposite. Indeed, DSC results from our previous study 27 showed that the melting point of the hard phase crystallites was approximately 15 °C higher in the nanocomposite compared to that of the neat PU.…”
Section: Resultsmentioning
confidence: 86%
“…The fracture toughnesses (K C ) were determined from spall tests that had similar values of shock stresses (0.96 GPa for the neat PU and 0.99 GPa for the nanocomposite). The fracture toughnesses were found to be 3.41 and 4.13 MPa m 1/2 for the neat PU and nanocomposite, respectively 27 .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations